ETIOLOGY AND DRUG SENSITIVITY PATTERN OF URINARY TRACT PATHOGENS IN DISTRICT MARDAN, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
A urinary tract infection is an infection that attacks the urinary tract. Infection of the upper urinary tract is termed pyelonephritis (kidney infection), whereas infection of the lower urinary tract is referred to as cystitis (bladder infection). Symptoms of cystitis include dysuria and increased urine frequency. In addition to the symptoms of cystitis, pyelonephritis can also cause fever and flank discomfort. Urinary tract infections are more prevalent in females than in males. Samples were obtained from individuals of varying ages and sexes at Mardan Medical Complex, Bacha Khan Medical Complex, and Benazir Bhutto Hospital in Mardan, using sterile containers that were properly labelled. After that, the samples were inoculated onto medium without cysteine and lysine electrolytes. Using biochemical testing and gramme staining, the pathogens were identified. Sensitivity testing was conducted on Muller Hinton medium using the Kirby-Bauer technique. Out of 143 samples, five (5) distinct urinary tract pathogens were identified; 97 of these samples tested positive for E. coli, 8 for Pseudomonas aeruginosa, 17 for Enterobacter species, 13 for Staphylococcus aureus, and 8 for E. faecalis. Compared to men, women experienced urinary tract infections more frequently. Between the ages of 21–40 and 41–60, urinary tract infections were more common.